Demokrasi Dalam Cengkeraman Oligarki: Tantangan Keadilan Dalam Sistem Politik Indonesia - Afrilia Era Vazira (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Democracy is basically a system of government that places the people as the holders of the highest sovereignty and aims to realize social justice as reflected in the values of Pancasila and the 1945 Constitution. However, in practice, democracy in Indonesia still faces serious challenges in the form of strengthening oligarchic practices in the political system. This study aims to analyze the influence of oligarchs on just democracy, the factors that cause oligarchs to continue to develop, and legal measures that can be taken to reduce this dominance. The research uses a normative legal method with a qualitative approach through literature studies. The results of the study show that oligarchic practices influence political processes, public policy, and law enforcement through the dominance of economic and political elites. This condition is strengthened by the weak internal democracy of political parties, high political costs, and low transparency of political funding. Therefore, political funding reforms, strengthening the independence of law enforcement agencies, and increasing public participation are needed to realize a more fair, transparent, and public-interest-oriented democracy.